Sensitivity to Inflectional Morphology in a Non-native Language: Evidence From ERPs - Coughlin, Caitlin E.; Fiorentino, Robert; Royle, Phaedra; Steinhauer, Karsten (Frontiers in Communication, 2019)
The extent to which non-native speakers are sensitive to morphological structure during language processing remains a matter of debate. The present study used a masked-priming lexical decision task with simultaneous electroencephalographic (EEG) recording to investigate whether native and non-native speakers of French yield behavioral and brain-level responses to inflected verbs. The results from reaction time and EEG analyses indicate that both native and non-native French speakers were indeed sensitive to morphological structure, and this sensitivity cannot be explained simply by the presence of orthographic or semantic overlap between prime and target. Moreover, sensitivity to morphological structure in non-native speakers was not influenced by proficiency (as reflected by the N400); lower-level learners show similar sensitivity at the word level as very advanced learners. These results demonstrate that native-like processing of inflectional morphology is possible in adult learners, even at lower levels of proficiency, which runs counter to proposals suggesting that native-like processing of inflection is beyond the capacity of non-native speakers.